Study on methods to extract high contrast image in active dynamic thermography. Issue 3 (2nd October 2019) - Saxena, Ashish; Raman, Vignesh; Ng, E. Y. K.
ABSTRACT: In the present study, image reconstruction methods are applied in active dynamic thermography (ADT) to visualize the superficial blood vessel with high contrast. ADT is performed on the left forearm of a human subject by applying cooling based external thermal stimulation. Both non-parametrized, viz. sequence image, sequentially subtracted image, Discrete Fourier Transformation (phase and amplitude image), and Thermographic Signal Reconstruction (TSR), and parametrized, viz. Tau time (τ ), d T n o r m, t 90 − 10 n, and Tissue Activity Ratio ( T A R ), types of image reconstruction methods are used. To perform a quantitative comparison, among the image reconstruction methods, the image contrast value is evaluated. While sequentially subtracted image provides a high contrast image in non-parametrized image reconstruction methods, for parametrized image reconstruction methods, it is T A R . Among all the methods considered, T A R provides the best contrast image followed by τ image method.